2015
DOI: 10.1002/jrs.4837
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of the microstructure of ion‐irradiated nuclear ceramics by in situ Raman spectroscopy

Abstract: Raman spectroscopy is an efficient technique for studying the evolution of microstructure of materials under irradiation. For that purpose, a Raman spectrometer has been recently installed at the JANNUS‐Saclay platform. In this paper, we describe the new setup for in situ experiments. These in situ experiments allowed following the microstructural evolution of different materials (SiC, ZrO2 and B4C) as a function of ion fluence on a single sample (either single crystal or polycrystalline ceramics) under the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 66 publications
0
27
0
Order By: Relevance
“…Therefore, the Si–C band areas (except for the 655‐cm −1 peak) were used to estimate the damage level in SiC, as discussed below. For homonuclear C–C bonds, it is not clear whether the D and G peaks involving graphite structures are first produced at low fluences, as observed in the case of the ion‐irradiated 6H–SiC, because the signal‐to‐noise ratio of the C–C bands is quite low in this study.…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…Therefore, the Si–C band areas (except for the 655‐cm −1 peak) were used to estimate the damage level in SiC, as discussed below. For homonuclear C–C bonds, it is not clear whether the D and G peaks involving graphite structures are first produced at low fluences, as observed in the case of the ion‐irradiated 6H–SiC, because the signal‐to‐noise ratio of the C–C bands is quite low in this study.…”
Section: Resultsmentioning
confidence: 66%
“…The spectra for the as‐grown nanocrystalline SiC films on Si are shown in Figure b, which exhibit weak Si–C TO and LO peaks as well as a broad plateau between the two peaks. This plateau is attributed to the scattering from the disordered crystal structure and/or GBs . In addition to the TO and LO peaks (centered at ~795 and 965 cm −1 ), highly disordered/amorphous SiC peaks at 766 and 870 cm −1 and a slightly disordered SiC peak at ~930 cm −1 are needed to fit the spectra well, as shown in Figures S3 and S4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Miro et al monitored the microstructure of ion‐irradiated nuclear ceramics by in situ Raman spectroscopy. Raman spectroscopy gives insight on these evolutions at the level of bonds given by specific phonon modes, in good agreement with Rutherford backscattering channeling (RBS/C), X‐ray diffraction (XRD), or transmission electron microscopy (TEM) data, which provide information at a long‐range scale . Sharma described a novel Raman spectroscopic approach to identify polymorphism in leflunomide through a combined experimental and theoretical study.…”
Section: Solid‐state Studiesmentioning
confidence: 64%
“…Phonon peak positions also shifts towards lower wave number with increasing fluence and is attributed to stress relaxation. Raman spectroscopy has also been found to be an efficient technique for studying the evolution of microstructure of materials under irradiation and has been successfully applied in a number of nuclear ceramics, graphite, glasses and spinels, and so forth to determine nature of phases before and after irradiation, stress accumulation induced by irradiation, and to evaluate lattice damage. In 100‐MeV O 7+ irradiated nano zinc ferrites, it is observed that fluence of ion beam and the crystalline size of the pristine target affect the Raman modes .…”
Section: Introductionmentioning
confidence: 99%